Adventure Therapy With Youth. (March 2014) - Norton, Christine Lynn; Tucker, Anita; Russell, Keith C.; Bettmann, Joanna E.; Gass, Michael A.; Gillis, H.L. "Lee"; Behrens, Ellen
This state of knowledge article provides an overview of Adventure Therapy (AT) as it is practiced with adolescents in North America, presenting (a) current findings in AT research with adolescents, (b) critical issues in AT, (c) the need for training and professional development in AT, and (d) professionalization in AT. Implications of current findings in AT research for practitioners, researchers, and consumers of AT services are also discussed.